EVALUASI PEKERJAAN PEMBANGUNAN SMAN 2 BUKITTINGGI MENGGUNAKAN METODE FISHBONE - Masril Masril (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Project delays are one of the most common problems in construction projects and may lead to increased project costs, reduced labor productivity, and failure to meet the planned project schedule. This study aims to identify the factors causing delays in School Buldings project and determine the dominant causes using the Fishbone Diagram and Pareto Diagram methods. This study employed a descriptive quantitative approach. Data were collected through field observations, interviews, documentation, and questionnaires distributed to project personnel. The collected data were analyzed by assigning impact and frequency scores using a five-point Likert scale. The risk score for each factor was obtained by multiplying the impact and frequency values. The identified causes were then classified into six categories of the Fishbone Diagram, namely Man, Material, Machine, Method, Measurement, and Environment. Furthermore, a Pareto Diagram was used to determine the priority factors contributing to project delays. The results indicate that the Man (Labor) category is the most dominant cause of project delays. The factors shortage of workers and low labor productivity obtained the highest score of 25.00, followed by poor worker discipline with a score of 19.50. Other significant factors include unrealistic work scheduling in the Method category with a score of 14.25, and high rainfall in the Environment category with a score of 12.00. Meanwhile, factors in the Machine category had relatively low influence, with the highest score being 3.63. The Pareto analysis showed that most project delays were caused by labor-related factors and work methods. Therefore, these factors should be prioritized in implementing corrective actions.It can be concluded that improving labor productivity, increasing the number of skilled workers according to project requirements, enhancing worker discipline, preparing more realistic work schedules, and strengthening project supervision are essential strategies to minimize delays in housing construction projects.Keywords: Project Delay, Fishbone Diagram, Pareto Diagram, Construction Project Management, school Buldings